Upaya Meningkatkan Teknik Dasar Long Service Bulu Tangkis dengan Menggunakan Metode Drill pada Siswa Kelas VI MIN 4 Kebumen - Mokhamad Parmadi; Nur Rohman (Journal on Education, 2025)
This study aims to improve the basic long service technique in badminton among sixth-grade students at MIN 4 Kebumen through the application of the drill method. The research employed Classroom Action Research (CAR) with two cycles, each consisting of planning, action, observation, and reflection stages. The study involved 26 students (9 boys and 17 girls) as subjects. The instruments used were skill tests, observation sheets, and documentation. The results showed a significant improvement in long service skills. The average student score increased from 48.25 in the pre-cycle to 52.10 in the first cycle and 77.17 in the second cycle. Furthermore, the percentage of students reaching the "Good" and "Very Good" categories increased from 12% in the pre-cycle to 77% in the second cycle. These findings highlight the effectiveness of the drill method in badminton learning. This study recommends utilizing the drill method in physical education to enhance students' motor skills.